Improved One-Pot, Four-Component Strategy to Access Functionalized Dihydropyridines by Using 4-(N,N-Dimethylamino)pyridine as a Catalyst - Ramesh, Rathinam; Arivazhagan, Mani; Malecki, Jan Grzegorz; Lalitha, Appaswami (Synlett, 2018)
A convenient strategy has been developed for the synthesis of structurally diverse novel 1,4-dihydropyridine frameworks bearing a 3-nitrophenyl moiety through a one-pot, four-component reaction with 4-(N,N-dimethylamino)pyridine as a catalyst at room temperature. This tandem process proceeds more effectively than previous catalytic processes.
Keywords: dimethylaminopyridine; nitrophenyldihydropyridines; multicomponent reactions; nitriles; amines; organocatalysis